How strong is the causal relationship between globalization and energy consumption in developed economies? A country-specific time-series and panel analysis. Issue 13 (16th March 2018) - Shahbaz, Muhammad; Shahzad, Syed Jawad Hussain; Mahalik, Mantu Kumar; Sadorsky, Perry
ABSTRACT: We examine the causal relationship between globalization, economic growth and energy consumption for 25 developed economies using both time series and panel data techniques for the period 1970–2014. Due to the presence of cross-sectional dependence in the panel (countries from Asia, North America, Western Europe and Oceania), we employ the cross-sectional augmented IPS test to ascertain unit root properties. The cointegration test results indicate the presence of a long-run association between globalization, economic growth and energy consumption. Long-run heterogeneous panel elasticities are estimated through the common correlated effects mean group estimator and the augmented mean group estimator. The empirical results reveal that, for most countries, globalization increases energy consumption. In the USA and UK, globalization is negatively correlated with energy consumption. The causality analysis indicates the presence of the globalization-driven energy consumption hypothesis. This empirical analysis suggests insightful policy guidelines for policy makers using globalization as an economic tool to utilize energy efficiently for sustainable economic development in the long run.